2005
DOI: 10.1148/radiol.2371031842
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of MR Imaging with Liver-specific Contrast Agent: U.S. Multicenter Phase III Study

Abstract: Compared with precontrast MR imaging, postcontrast MR imaging with Gd-EOB-DTPA demonstrated improved sensitivity for lesion detection in the majority of blinded readers, with no substantial adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
168
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(177 citation statements)
references
References 29 publications
4
168
2
2
Order By: Relevance
“…Previous studies have demonstrated that Gd-EOB-DTPA is well tolerated and has no substantial adverse events and minor adverse events of 5.9% (6,7,19). In fact, there were no severe adverse effects in our study population.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have demonstrated that Gd-EOB-DTPA is well tolerated and has no substantial adverse events and minor adverse events of 5.9% (6,7,19). In fact, there were no severe adverse effects in our study population.…”
Section: Discussionsupporting
confidence: 50%
“…For gadobenate dimeglumine-enhanced MRI, the reported imaging window for the acquisition of hepatobiliary phase images is 40-180 minutes after injection of the contrast material (30)(31)(32). In contrast, gadoxetate disodium-enhanced hepatobiliary phase images can be obtained after a shorter delay time of 20 minutes (13,17,29,(33)(34)(35), and some studies have implied that a scan delay for the acquisition of gadoxetate disodium-enhanced hepatobiliary phase images can be even further reduced (20,21). In a study including 23 patients with hepatic metastases, Reimer et al (20) showed that lesion-to-liver contrast-to-noise ratios of hepatic metastases are comparable between gadoxetate disodium-enhanced 10-minute and 20-minute delayed images but did not compare the sensitivity for the two image sets.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced MR imaging has been used for the diagnosis of HCC. The detection rate of liver nodules was reported to be higher than that of CT [28,29]. However, the most lesions they assessed were metastatic tumors and the rate of detection for small HCC lesions (\10 mm) was low.…”
Section: Discussionmentioning
confidence: 94%